Nitro-polycyclic aromatic hydrocarbons – gas–particle partitioning, mass size distribution, and formation along transport in marine and continental background air - G. Lammel; M. D. Mulder; P. Shahpoury; P. Kukučka; H. Lišková; P. Přibylová; R. Prokeš; G. Wotawa (Atmospheric Chemistry and Physics, 2017)
Nitro-polycyclic aromatic hydrocarbons (NPAH) are ubiquitous in polluted air but little is known about their abundance in background air. NPAHs were studied at one marine and one continental background site, i.e. a coastal site in the southern Aegean Sea (summer 2012) and a site in the central Great Hungarian Plain (summer 2013), together with the parent compounds, PAHs. A Lagrangian particle dispersion model was used to track air mass history. Based on Lagrangian particle statistics, the urban influence on samples was quantified for the first time as a fractional dose to which the collected volume of air had been exposed. At the remote marine site, the 3–4-ring NPAH (sum of 11 targeted species) concentration was 23.7 pg m−3 while the concentration of 4-ring PAHs (6 species) was 426 pg m−3. The most abundant NPAHs were 2-nitrofluoranthene (2NFLT) and 3-nitrophenanthrene. Urban fractional doses in the range of < 0.002–5.4 % were calculated. At the continental site, the Σ11 3–4-ring NPAH and Σ6 4-ring PAH were 58 and 663 pg m−3, respectively, with 9-nitroanthracene and 2NFLT being the most concentrated amongst the targeted NPAHs. The NPAH levels observed in the marine background air are the lowest ever reported and remarkably lower, by more than 1 order of magnitude, than 1 decade before. Day–night variation of NPAHs at the continental site reflected shorter lifetime during the day, possibly because of photolysis of some NPAHs. The yields of formation of 2NFLT and 2-nitropyrene (2NPYR) in marine air seem to be close to the yields for OH-initiated photochemistry observed in laboratory experiments under high NOx conditions. Good agreement is found for the prediction of NPAH gas–particle partitioning using a multi-phase poly-parameter linear free-energy relationship. Sorption to soot is found to be less significant for gas–particle partitioning of NPAHs than for PAHs. The NPAH levels determined in the south-eastern outflow of Europe confirm intercontinental transport potential.